Influence of pH on the conformation and stability of mismatch base-pairs in DNA. - Brown, T; Leonard, G; Booth, E; Kneale, G (1990)
A series of self-complementary dodecanucleotide duplexes containing two symmetrically disposed mismatches have been studied by pH-dependent, ultraviolet light melting techniques. The results indicate that A.C, and C.C mismatches are strongly stabilized by protonation and that the degree of stabilization of the A.C mismatch depends greatly on the flanking bases. In one case, a duplex containing two A.C mismatches is more stable than the native sequence below pH 5.5. The G.A mismatch displays conformational flexibility, with a protonated G(syn).A(anti) base-pair occurring in certain base stacking environments but not in others. The A.A and T.C mismatches are not stabilized at low pH. These solution studies correlate well with predictions based on X-ray crystallographic data.